Nutrition, Health and Athletic Performance - Enette Larson Meyer (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Optimal nutrition is fundamental for enhancing training, recovery and performance in sport. Therefore, research has aimed to determine the efficacy of appropriate intake of nutrients, fluids, and supplements and their role in exercise performance. The purpose of this Special Issue entitled "Nutrition, Health and Athletic Performance" is to highlight recent research examining aspects of sports nutrition and exercise performance. Manuscript submissions of original research, meta-analyses, or reviews of the scientific literature, which targets nutritional strategies to benefit performance and health, are welcome. Studies performed in humans are preferred given the applied nature of this issue.